Halil Merdem Bek's Understanding of Poetry in The Context of Classicism and Modernism - Can, Süleyman; Karataş, Yusuf (Fırat University, 2022)
Halil Merdem Bek, who lived in the most crisis-filled days of Ottoman and Syrian history, was one of the leading figures of literature and poetry from Syria. Merdem Bek argued that a true scholar of literature could not confine himself to only classical Arabic literature, and that he would also have a strong command of Western literature and ideas. Therefore, in addition to literary schools such as the Mehcer and İhyâ group, he was also interested in the literary trends in Europe and received doctorate education in England for this reason. In his poems, the influence of his teachers, modern literary groups and Europe is apparent. In his poems, he occasionally adhered to the unification of subject matter within couplets, and other times he dealt with separate topics. On the one hand, he was meticulous to employ the language correctly and to write rhymed poems with strong compositions, while writing poems in the classical tradition. On the other hand, he was able to incorporate the modern literary style in his poems through the use of a variety of themes and sentence structures. In the present study, the life of Halil Merdem Bek was briefly summarized, and his educational status and literary persona was discussed separately. Afterwards, the factors affecting his personality (his teachers, his interest towards the Mehcer and İhyâ group and the doctorate education he received in England) were discussed, followed by an analysis of his linguistic and stylistic features. Finally, his tendency towards classical and modern poetry was investigated. Through the information obtained within this context, an evaluation was made on the subject in the conclusion section.

Öz: Osmanlı ve Suriye tarihinin en buhranlı günlerinde yaşayan Halil Merdem Bek,Suriye’nin yetiştirdiği önde gelen edebiyatçı ve şairlerdendir. O, gerçek edebiyatçının sadece klasik Arap edebiyatıyla yetinemeyeceğine; Arap edebiyatının yanında batı edebiyatı ve fikirlerini de iyi bilmesi gerektiğine inanmaktadır. Bundan dolayı Mehcer ve İhyâ grubu gibi edebî ekollerin yanında Avrupa’daki edebî akımlarla da ilgilenmiş, bunun için İngiltere’de doktora eğitimi almıştır.Yazdığı şiirlerinde hocalarının, modern edebî grupların ve Avrupa’nın etkisigörülmektedir.Şiirlerinde kimi zaman beyitler arasındaki konu birliğine riayet etmiş, kimi zaman da farklı konular işlemiştir. Bir yandan dili düzgün kullanmaya dikkat ederek sağlam terkiplerle kafiyeli şiirler yazarak klasik üsluba uygun şiirler yazarkendiğer yandan da farklı tema ve cümle kurgularıyla modern edebî üslubu şiirlerine yansıtmayı başarmıştır. Bu çalışmanın konusu, Halil Merdem Bek’in hayatına kısaca yer verilmesi, eğitim durumu ve edebî kişiliğinin incelenmesi şeklindeolmaktadır. Sonra edebî kişiliğini etkileyen faktörler olan hocaları,Mehcer ve İhyâ grubuna olan ilgisi ile İngiltere’de aldığı doktora eğitimi üzerinde durulmuştur. Daha sonra daşiirinin dil ve üslup özellikleri incelenmiştir. Aynı andaklasik ve modern şiire olan eğilimi üzerinde durulmuştur.Bu bağlamda elde edilen bilgilerle sonuç kısmında konuyla ilgili değerlendirme yapılmıştır.
Klasizm ve Modernizm Bağlamında Halil Merdem Bek’in Şiir Anlayışı
Keywords: Religious Studies; Din Araştırmaları